The Development of Mathematical Worksheet based on Surrounding Environment with Problem Based Learning Model to Improve Creative Thinking Ability - Safira, Amalia Fitri Ayu; Susilo, Bambang Eko (Department of Mathematics, Universitas Negeri Semarang, 2022)
This research aims to develop mathematical worksheet product based on surrounding environment in the problem based learning in flat-side space material and to improve creative thinking ability. Using Research and Development with 4D-Thiagarajan model modified 3D (consist of define, design and, develop). The result show that student worksheet is valid, easy to understand, and effective to improve creative thinking ability. The worksheet is valid with an average percentage of 88.60%. Next, the worksheet is easy to understand with a percentage of 83% using a practice tests with a cloze test. Meanwhile, the worksheet can improve creative thinking ability through the paired T-test and right-tailed T-test which was strengthened by the N-gain test with a result of 0.596 on the medium criteria. The worksheet is packaged an atrractive presentation targeting 8th grade and has received e-copyright by Electronic Intellectual Wealth General Directory.